On the time of existence of weak discontinuity waves in poroelastic materials - Wilmański, K. (Archives of Mechanics, 1998)
In the paper, we consider the possibility of the growth of strong discontinuity waves in the two-component poroelastic materials. We use the model with the hyperbolic set of field equations described in the paper by K. Wilmański [8]. It is shown that indeed, the critical time (i.e. the maximum time of existence of classical solutions) is finite and it assumes realistic values for real physical systems, such aa biological tissues.